Pengaruh Pengaruh dewan komisaris independen, kepemilikan manajerial dan kepemlikan institusional terhadap profitabilitas - Khotimah, Miftahul; Huda, Syamsul (FKIP Unswagati, 2025)
This This study aims to analyze the effect of independent commissioners, managerial ownership, and institutional ownership on profitability in textile and garment sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Profitability is measured using Return on Assets (ROA). The research employs a quantitative method with a descriptive and verificative approach. The sample was determined using purposive sampling, resulting in 9 companies with a total of 45 data samples. The data analysis technique used is multiple linear regression. The results of the study show that the significance obtained is 0.021 < 0.05 with a t-table value (36-3 = 33) of 2.03452, and the calculated t-value > t-table (2.430 > 2.03452), which means that (1) partially, independent commissioners have a significant positive effect on profitability. A significance value of 0.021 < 0.05 with a t-table (36-3 = 33) of 2.03452 and a calculated t-value > t-table (2.423 > 2.03452) indicates that (2) managerial ownership has a significant negative effect on profitability. Furthermore, a significant value of 0.010 < 0.05 with a t-table (36-3 = 33) of 2.03452 and a calculated t-value > t-table (2.737 > 2.03452) indicates that (3) institutional ownership also has a significant negative effect on profitability. (4) Simultaneously, the f-table value (36-3 = 33) is 2.89, while the obtained f-value is 3.969 > 2.89 with a significance of 0.016 < 0.05, which means that independent commissioners, managerial ownership, and institutional ownership together have a significant effect on the profitability of textile and garment sub-sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Keywords: independent commissioners, managerial ownership, institutional ownership, profitability